2018
DOI: 10.3390/ijerph15112485
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic Potency of Airborne Polycyclic Aromatic Hydrocarbons in Relation to the Particle Fraction Size

Abstract: Polycyclic aromatic hydrocarbons (PAHs) that are bound to particulate matter can have adverse effects on human health. Particle size plays an important role in assessing health risks. The aim of this study was to compare concentrations of PAHs bound to particle fractions PM10, PM2.5, and PM1, as well as to estimate their carcinogenic potency and relative contributions of the individual PAHs to the carcinogenic potency in relation to the size of the particle. Measurements of ten PAHs were carried out in 2014 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 49 publications
(148 reference statements)
4
22
0
Order By: Relevance
“…PAHs are ubiquitous environmental toxicants and AhR ligands. However, until now, only existing air quality standards focus exclusively on benzo(a)pyrene (B[a]P), a member of PAH, bound to the PM 10 fraction (Pehnec and Jakovljević, 2018), with few results of the effects of PAH binding to PM in human health.…”
Section: Skin Aging and Air Pollutionmentioning
confidence: 99%
“…PAHs are ubiquitous environmental toxicants and AhR ligands. However, until now, only existing air quality standards focus exclusively on benzo(a)pyrene (B[a]P), a member of PAH, bound to the PM 10 fraction (Pehnec and Jakovljević, 2018), with few results of the effects of PAH binding to PM in human health.…”
Section: Skin Aging and Air Pollutionmentioning
confidence: 99%
“…Studies regarding PAH in PM 1 were carried out only at a few urban locations in Europe [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. It was found that the levels varied significantly between heating and non-heating season [ 22 , 23 , 26 ]. The highest concentrations were observed during winter in areas where coal and wood burning were used for heating [ 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transportation is also a source of polycyclic aromatic hydrocarbons (PAHs) whose concentrations increase especially in winter. These are detrimental to healt, both as isolated compounds and as a component of dust [8]. Diesel engine exhaust fumes are particularly critical which -besides PAHs rich in nitro groupscontain carbon and metals [2].…”
Section: Sources Of Air Pollutionmentioning
confidence: 99%